Scattered Abroad: The Ukrainian Theatrical Emigration Seen through the Fate of the Actor Fedir Fedorovych - Полякова, Юліана (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
The article concerns the life and activities of the actor FedirFedorovych. His fate was typical for a great number of Ukrainian intelligentsia, who found themselves in emigration after WWII, producing impact on the formation of Ukrainian diaspora culture. Purpose. The author’s intention has been to follow and analyze the main stages in the actor FedirFedorovych’s creative activities within the context of the Ukrainian theater’s development. The research is based on studying the contemporary press and the Fedorovyches’ family archive. Methods. The author has used the cultural-historical method, which implies searching and collecting information concerning the exact object, processing this information, analyzing its correlation with historical and cultural background, and defining the significance of the actor’s activities for development of the theater art in a certain period. Results. The early period of Fedorovych’s activities was closely connected with Kharkiv. The actor was born in the town of Uman in 1895. He took part in the fighting during the First World War. In 1920 he studied at the workshop under Kyidramte (Kyiv Drama Theater), under the guidance of Les Kurbas. Later he acted on stages of the I. Franko Theater, the First Odessa Workers and Peasants’ Theater led by Ye. Kokhanenko, Chervonozavodsky Theater in Kharkiv, the Kharkiv Theater of the Revolution, the Leninist Komsomol Theater in this city. He played mostly character and comic personages in performances after Ukrainian and foreign playwrights. In 1940Fedorovych left Kharkiv for Chernivtsi, where the Leninist Komsomol Theater was transferred. After the Soviet Union got involved in WWII, Fedorovych returned to Kharkiv, staying there under the Nazis. At the time he worked at the T. Shevchenko Theater, then, in 1943, left the city together with the retreating Hitlerite troops. When Germany was defeated, Fedorovych experienced a lot of wandering, in the end finding himself in the “Orlyk” displaced persons’ camp, Bavaria, and founded a theater there. The latter existed until 1950. There Fedorovich as a director put on the stage a number of productions after “The Mistress of the Inn” by C. Goldoni; “Rosy Weaverbird” by Ya. Mamontov; “Martyn Borulia” by I. Karpenko-Karyi; “Going for the First Hangout” by S. Vasylchenko; and some others. In 1950Fedorovich, together with his family, was granted entrance to the U.S., where he organized an amateur theater in NewHaven, Conn. He also worked as both director and actor of the Ukrainian Opera Ensemble (NewYork, NY). Inthelatter, heplayedin “NatalkaPoltavka” byI. Kotliarevsky (1958); “TheMatchmakinginHoncharivka” byH. Kvitka-Osnovyanenko (1963); operas “The Black Sea People” by M. Lysenko (1965); “Cossacks in Exile” by S. Hulak-Artemovsky (1972). Novelty of research. This research is the first one to present an integral evaluation of FedirFedorovych’s creative activities as typical for a member of theatrical community of Ukraine. It also introduces the documents from the Fedorovyches’ family archive into scientific parlance. Conclusions. Fedir Fedorovych’s creative activities testify to the fact that a number of Ukrainian actors in exile proved to be able both to maintain the high level of acting, worked up in the native country, and to preserve the classical repertoire, thus passing their experience to the next generations.